THE EFFECTIVENESS OF LIMA SAHABAT TO ENHANCE THE STUDENTS VOCABULARY ACHIEVEMENT - Agung, Muhammad (English Language Education Study Program, 2022)
This study is to more clearly identify the problems of students vocabulary achievement in distance learning and how the use of Android applications as a way of mobile learning to address these problems. This study aims to examine the effectiveness of the mobile learning concept with the use of learning source named Lima Sahabat for learning vocabulary among seventh grade students of junior high school. A Pre-experimental research design was used (one group Pre-Test and Post-Test design). The population in this study were all the seventh-grade students (64 students) and the sample was the class VII B (31 students) which was chosen by using purposive sampling. The finding of the data analysis showed that the mean score of the Post-Test (88.84) was higher than the Pre-Test (55.83) with the improvement percentage was 59.13% and the success rate of the students score in difference of the Pre-Test and the Post-Test showed that the pvalue = 0.00 was less than the α = 0.05 which means that there was a significant improvement of the students vocabulary achievement.